Highly Enhanced Photoluminescence of Monolayer MoS2 with Self‐Assembled Au Nanoparticle Arrays. Issue 21 (10th August 2017) - Zeng, Yi; Li, Xing; Chen, Weibing; Liao, Jianhui; Lou, Jun; Chen, Qing
Abstract: Monolayer MoS2 normally has weak photoluminescence (PL) because of the poor light absorption due to the atomic thickness. Here, the highly enhanced PL of chemical vapor deposited (CVD)‐grown monolayer MoS2 with uniform self‐assembled sub‐monolayer Au nanoparticle arrays is reported. The PL intensity of monolayer MoS2 can be enhanced by up to 200 times. The dependence of the enhancement factor upon the excitation wavelength, the density of Au nanoparticles, and the thickness of the dielectric layer, is systematically investigated. The results indicate that the PL enhancement indeed stems from the local surface plasmon resonance of Au nanoparticles. The study provides a bottom‐up, low‐cost, large scale, and highly effective route to enhance the PL of CVD‐grown monolayer MoS2 . Abstract : The highly enhanced photoluminescence (PL) of chemical vapor deposited (CVD)‐grown monolayer MoS2 with uniform self‐assembled sub‐monolayer Au nanoparticle arrays is reported. The PL intensity of monolayer MoS2 can be enhanced by up to 200 times. The study provides a bottom‐up, low‐cost, large scale, and highly effective route to enhance the PL of CVD‐grown monolayer MoS2 .